2014
DOI: 10.1007/s40266-014-0208-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pharmacist Medication Review Services on Drug-Related Problems and Potentially Inappropriate Prescribing of Renally Cleared Medications in Residents of Aged Care Facilities

Abstract: DRPs are common in aged care facilities and the impact of medication review services appears to be high. CKD is also common among residents of aged care facilities, and inappropriate prescribing of renally cleared medications was also prevalent, warranting attention to regular renal function monitoring and appropriate drug and dose selection in residents of aged care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(100 citation statements)
references
References 41 publications
5
84
0
11
Order By: Relevance
“…The START/STOPP criteria have been gaining prominence in Europe [10] and there are reports using the McLeod criteria [11], Priscus list [12] and even nationally developed classifications [13, 14]. However, few reports of pharmacist-led medication reviews focus on the identification of DRPs, and these have either used the Pharmaceutical Care Network Europe classification [15, 16] or the DOCUMENT classification [17]. The Dader method has been used in nursing homes [18] but, to our knowledge, no paper has yet described the nature of DRP detected using the Granada classification to guide pharmacist-led medication reviews [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…The START/STOPP criteria have been gaining prominence in Europe [10] and there are reports using the McLeod criteria [11], Priscus list [12] and even nationally developed classifications [13, 14]. However, few reports of pharmacist-led medication reviews focus on the identification of DRPs, and these have either used the Pharmaceutical Care Network Europe classification [15, 16] or the DOCUMENT classification [17]. The Dader method has been used in nursing homes [18] but, to our knowledge, no paper has yet described the nature of DRP detected using the Granada classification to guide pharmacist-led medication reviews [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Polypharmacy is common among older people with multiple chronic conditions. This situation is of particular concern as older people are more sensitive to drugs and adverse drug reactions (ADRs) than younger individuals [2, 4]. The changes in neurotransmitter substances that occur in people with dementia make this patient group especially vulnerable to the effects of drugs, including ADRs [1, 2, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs such as morphine and glibenclamide that have active metabolites may cause ADRs [10, 11]. Estimation of renal function is thus important when prescribing renally excreted drugs to older people to avoid inappropriate prescribing, which is defined as “a situation where risk from the adverse effects of a prescribed medication outweighs the desired clinical benefits of treating a particular condition” [4]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This medication review should be particularly focused on benzodiazepines, other psychotropic medications, and medicines that contribute to a high drug burden index (ie, those with anticholinergic or sedative properties). 6,[32][33][34] Other interventions to prevent falls have been multifactorial in nature and have addressed risk factors pertaining to the individual (eg, strength and balance training) as well as his or her ability to safely interact with the environment. A meta-analysis by Cameron et al 35 reported that multifactorial interventions reduce falls and risk of falling in hospitals and may do so in nursing care facilities.…”
Section: Nonpharmacologicalmentioning
confidence: 99%